Non-family management succession in family businesses - Domanowska, Justyna (Lodz University Press, 2024)
The research presented in the paper focused on non-family management succession. The majority of family businesses in Poland, founded in the 1990s, are in the process of or are approaching a generational change. The succession process is one of the most difficult stages that family businesses go through. Proper selection of a successor increases the probability of survival and development of the company. The most common solution is to choose a successor from the family circle. However, there are situations when such a solution is difficult or even impossible. Indicating non-family management succession as a good alternative to family succession may be of great importance for the further functioning of a family business on the market. The subject of the empirical part is the analysis of factors influencing the decision to transfer the management to a person, unrelated to the family. Factors determining whether the company should remain in the family despite transferring the management of the company to an external manager.